Mounting‐insensitive nonpolarizing guided‐mode resonance filters for optical communications. Issue 12 (11th October 2018) - Ren, Zhibin; Sun, Yahui; Zhang, Shuqing; Hu, Jiasheng; Lin, Zihao
Abstract: Mounting‐insensitive nonpolarizing guided‐mode resonance filters (GMRFs) for the optical communication wavelength O‐band and C‐band have been designed and fabricated. The rigorous coupled‐wave analysis (RCWA) is used to calculate the reflection spectra of the designed GMRFs. The grating structures of the GMRFs are patterned by interference lithography with two ultraviolet laser beams. The reflection spectra of the fabricated samples at different incident angles are measured by rotating a motorized stage. Compared with previous reported one‐dimensional nonpolarizing GMRFs, the tolerances of conical angle of the fabricated samples are remarkably improved.